KEUNGGULAN MEKANISME KELAS KERJA SAMA PERGURUAN TINGGI DAN MITRAS DUDI (STUDI KASUS: POLITEKNIK NEGERI JAKARTA) - Arnanda, Rachmat; Saidatuningtyas, Ifa; Ardhan, Dhea Tisane (Politeknik Negeri Jakarta, 2024)
Universities are required to produce quality graduates according to the constant developments. To get quality graduates, universities must adjust the curriculum according to what is needed so that workforce absorption is in line with market demand. Collaboration mechanism becomes a way to collaborate with other parties to develop and increase the competitiveness of higher education, strengthen the image and quality of higher education. One way for Politeknik Negeri Jakarta (PNJ) to keep up with the change in of business and industry sector is to collaborate with industry, and in this case is with Mitras DUDI. The research used qualitative methods with a descriptive approach. This research aimed to present the phenomenon of the superiority of the cooperative class mechanism from the perspective of students, universities, and users (industry), as well as to see the absorption of cooperative class graduates by using data triangulation to ensure the quality and completeness of the data. Based on the results of data processing obtained from interview methods, participant observation, and document record analysis, an explanation regarding the phenomenon of the superiority of the cooperative class mechanism was obtained from the perspective of students, universities, and users (industry) through the cooperative class program. One of the advantages is that there is a greater opportunity for the cooperative class graduates to compete and work in the industrial and business sectors.